2010
DOI: 10.3324/haematol.2009.008870
|View full text |Cite
|
Sign up to set email alerts
|

Histone deacetylase inhibition modulates cell fate decisions during myeloid differentiation

Abstract: The online version of this article has a Supplementary Appendix. BackgroundThe clinical use of chromatin-modulating drugs, such as histone deacetylase inhibitors, for the treatment of bone marrow failure and hematopoietic malignancies has increased dramatically over the last few years. Nonetheless, little is currently known concerning their effects on myelopoiesis. Design and MethodsWe utilized an ex vivo differentiation system in which umbilical cord blood-derived CD34 + cells were treated with trichostatin A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
32
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 56 publications
3
32
0
Order By: Relevance
“…We have previously demonstrated that modulating protein acetylation in CD34 1 hematopoietic progenitors, by using lysine deacetylase inhibitors (KDACi), affects cell fate decisions during myeloid development. 35 These data suggested that the effects were the result of regulation of both histone and nonhistone proteins. Skokowa et al have demonstrated that treatment of myeloid progenitors with NAM stimulates neutrophil differentiation both in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…We have previously demonstrated that modulating protein acetylation in CD34 1 hematopoietic progenitors, by using lysine deacetylase inhibitors (KDACi), affects cell fate decisions during myeloid development. 35 These data suggested that the effects were the result of regulation of both histone and nonhistone proteins. Skokowa et al have demonstrated that treatment of myeloid progenitors with NAM stimulates neutrophil differentiation both in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 86%
“…Modulating acetylation by NAM or other KDACi could therefore be of importance for the treatment of neutropenia or functional neutrophil defects. 32,35,41 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gene silencing associated with the aberrant methylation of promoter region of CpG islands is an acquired epigenetic alteration that serves as an alternative to genetic events in the inactivation of tumor suppressor and other genes in human cancers. NaBu has been applied in cellular and molecular research (23,24), particularly in antitumor research (25)(26)(27)(28). It plays a vital role in vitamin D-induced apoptosis through PTEN upregulation, which has potential benefit in gastric cancer therapy (29).…”
Section: Discussionmentioning
confidence: 99%
“…VPA was reported to induce the expansion of CD34 + progenitors in mice in a concentration-dependent manner. 27 Furthermore, colonyforming units-spleen (CFU-S) assays and competitive repopulation assays showed that VPA increases proliferation as well as self-renewal of HSCs. 16 Here, we show that VPA increases the population of CD34 + CD90 + significantly.…”
Section: Discussionmentioning
confidence: 99%